Detection and discovery of plant viruses in Disporopsis through high-throughput sequencing - Li, Qiannan; Yang, Lianfu; Zhu, Ting; Yv, Xiyv; Zhang, Boxin; Li, Hongzhe; Hao, Junjie; Zhang, Lei; Ji, Pengzhang; Dong, Jiahong (Frontiers in Microbiology, 2024)
BackgroundDisporopsis, a member of the Liliaceae family and a perennial herb, is predominantly cultivated in southwestern and southeastern China. Its rhizome, referred to as Zhugenqi, serves as a traditional Chinese medicinal herb for the treatment of bone injuries. However, viral diseases have emerged as a significant challenge in the cultivation of Disporopsis.ObjectiveThe aim of this study was to identify and characterize viruses present in diseased samples of Disporopsis spp. using high-throughput sequencing (HTS) and reverse transcription-polymerase chain reaction (RT-PCR) to enhance the understanding of the virome associated with Disporopsis and to inform diagnostic and control strategies for viral diseases in this plant.MethodsDiseased samples of Disporopsis spp. were subjected to HTS and RT-PCR for virus identification. A total of five viruses were detected, including three novel viruses and two known viruses. The novel viruses were provisionally named Disporopsis chlorotic stripe virus (DCSV), Disporopsis pernyi-associated partitivirus (DaPTV), and Disporopsis pernyi-associated lispi-like virus (DaLV). Sequence identity and phylogenetic analyses were performed to confirm the novelty and taxonomic placement of these viruses.ResultsDCSV exhibited polyprotein sequence identities ranging from 47.6% to 83.6% with other potyviruses, with the highest identity (83.6%) shared with Polygonatum kingianum virus 5 (PKgV5). DaLV shared an amino acid sequence identity of 34.59% with maize suscal virus (MSV), and DaPTV shared an identity of 76.18–85.10% with Paris alphapartitivirus (ParAPV). Phylogenetic analyses supported the potential classification of the three novel viruses as new members of their respective genera. Two isolates of polygonatum mosaic-associated virus 1 (PMaV1) were identified in Disporopsis for the first time, showing divergences of 96.33% and 98.86% from existing isolates. RT-PCR analysis of 67 Disporopsis field samples collected from four cities in China revealed that more than half of the samples tested positive for at least one of the five viruses. PMaV1 and DaLV were the most prevalent, detected in 22 and 34 out of the 67 samples, respectively. Other viruses were detected at low rates and/or had limited distribution.ConclusionThis study provides insights into the virome infecting Disporopsis and offers valuable information for the diagnosis and control of viral diseases in this plant. The identification of five viruses, including three potential new members of their respective genera, contributes to the understanding of the viral threats to Disporopsis cultivation.